2018
DOI: 10.1007/978-3-319-90575-4_13
|View full text |Cite
|
Sign up to set email alerts
|

Natural Disasters and Firm Resilience in Italian Industrial Districts

Abstract: We carry out a firm-level empirical analysis to evaluate the economic impact of the sequence of earthquakes occurred in 2012 in the Italian region of Emilia-Romagna, and to address the question of whether the localization of a firm within an industrial district mitigated or exacerbated this impact. We estimate the effect of the earthquake on firms' performance via two alternative methods: Difference-InDifferences and Propensity Score Matching in levels and first-differences. Our findings suggest that the earth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…In the context of industrial districts (IDs), resilience is "an adaptive capability that allows a cluster to make changes to overcome internal and external disturbance and still function with its identity as a cluster" (Østergaard and Park, 2013: 4). Indeed, resilience has been used to identify and classify different evolutionary development paths (Martin and Sunley, 2011), to explain why some districts evolve while others disappear in the face of external challenges such as globalization, recession, and natural disasters (Cainelli et al, 2018;De Marchi et al, 2018).…”
Section: Resilience In Regions and Industrial Districtsmentioning
confidence: 99%
“…In the context of industrial districts (IDs), resilience is "an adaptive capability that allows a cluster to make changes to overcome internal and external disturbance and still function with its identity as a cluster" (Østergaard and Park, 2013: 4). Indeed, resilience has been used to identify and classify different evolutionary development paths (Martin and Sunley, 2011), to explain why some districts evolve while others disappear in the face of external challenges such as globalization, recession, and natural disasters (Cainelli et al, 2018;De Marchi et al, 2018).…”
Section: Resilience In Regions and Industrial Districtsmentioning
confidence: 99%
“…This paper is also related to the vast body of empirical literature assessing the disaster impact on firm performance. 8 According to recent studies using micro-level data, the destruction of physical capital due to natural disasters may be a good chance of upgrading it (Leiter et al 2009;Vu and Noy 2018;Okazaki et al 2019) or a bad one of decreasing productivity and the survival rates of firms (Tanaka 2015;Cainelli et al 2018;Cole et al 2019;Meltzer et al 2021). 9 Only a limited number of empirical studies examine the nexus between natural disasters and multinationals.…”
Section: Relation To the Literaturementioning
confidence: 99%
“…This paper is also related to the vast body of empirical literature assessing disaster impact on firm performance. 9 Recent studies using micro-level data have found that natural disasters destroy enormous amounts of physical capital, which may be a good chance of updating capital (Leiter et al, 2009;Vu and Noy, 2018;Okazaki et al, 2019) or a bad one of decreasing productivity and the survival rates of firms (Tanaka, 2015;Cainelli et al, 2018;Cole et al, 2019;Meltzer et al, 2021). 10 Only a limited number of empirical studies examined the nexus between natural disasters and multinationals.…”
Section: And Appendix 7)mentioning
confidence: 99%